Technical Efficiency of Irrigated Rice Production in Burkina Faso Water Control Infrastructures: A Stochastic Frontier Approach - Kabore, Daniel P (Asian Journal of Agriculture and Rural Development, 2016)
The present study examines the technical efficiency of irrigated rice production in Burkina Faso for the three irrigation systems: along the river at Kou, downstream the dam at Bagré and pumping system at Sourou. The results show that the overall technical efficiency is high: 87%. The estimates of the stochastic production frontier model indicate that chemical fertilizers and equipment expenses have a positive relationship with rice production, in contrast of the cropped area which comes as a complementary factor to equipment. The socio-economic factors that significantly reduce technical inefficiency are the household type and the age of the head of the household. The findings also revealed that increasing cropped area alone is not enough to increase rice production without a better access to fertilizers and to equipment implement (plows, harrows, and oxen). The pumping irrigation system operated at Sourou proved to be more technically inefficient than the system along the river at Kou valley. Therefore, in the current conditions, the option of the pumping irrigation system should be excluded from future irrigation scheme.